Agraphia due to Conversion Disorder (Functional Neurological Symptom Disorder) in an 8-year-old boy: a case report - Tran, Nhu Minh Hang; Le, Tran Tuan Anh; Nguyen, Vu Quoc Huy (Frontiers in Psychiatry, 2025)
Conversion disorder, a psychiatric condition characterized by neurological symptoms without organic etiology, is rare in children but can significantly impair functioning. This case report describes an 8-year-old boy presenting with sudden onset of hand tremors, inability to write, and recurrent abdominal pain following a three-month summer vacation and increased academic demands. Despite extensive neurological evaluations (MRI, EEG, EMG) showing no organic abnormalities, symptoms persisted, exacerbated by social isolation and secondary gains from family and school accommodations. Treatment with play therapy, cognitive therapy emphasizing fairness, and parental guidance to reduce overindulgence led to rapid symptom improvement within days. Follow-up over twenty months demonstrated sustained recovery and successful school reintegration. This case highlights the interplay of academic stress, psychological defense mechanisms, and secondary gains in pediatric conversion disorder, underscoring the efficacy of tailored psychological interventions and the importance of addressing familial dynamics to mitigate symptom persistence.